Estrategias de auditoría forense preventiva en el área de gestión de cartera de la EMPRESA Eléctrica Riobamba S.A. para el año 2024. - Amaguaya Morocho, Nancy Del Pilar (2025)
This research examines the vulnerabilities in the overdue portfolio processes of Empresa Eléctrica Riobamba S.A., aiming to reduce the risk of fraud and strengthen internal controls. The study is particularly relevant given the need for transparency and efficiency in activities involving public resources, especially in the utility sector, where the company operates. The primary objective was to develop preventive forensic audit strategies tailored to the specific use cases of Empresa Eléctrica Riobamba S.A., with the goal of preventing fraud and optimizing audit management. I employed a qualitative and descriptive methodology, based on a documentary study and supported by interviews with company staff. The findings reveal the specific weaknesses in the company’s current internal controls and propose strategies to address them through the implementation of advanced technologies and improved development plans. Key recommendations include the introduction of automated controls and monitoring systems, along with updates to internal policies. To conclude, the research successfully achieved its objective of developing preventive forensic audit strategies for the overdue portfolio processes of Empresa Eléctrica Riobamba S.A. for the year 2024.